Training need assessment report on livestock feed and forage production and utilization - Abdulkadir, Birhan; Gebreyes, Million; Mekonnen, Kindu (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The capacity development need assessment initiative is part of the feed and forage innovation value chain of the Accelerating Impact of CGIAR Climate Research in Africa (AICCRA) project of Ethiopian. AICCRA is a three years (2021-2023) project that operates in six African countries including Ethiopia. The project is supported by a grant from the International Development Association (IDA) of the World Bank and will enhance research and capacity-building activities by CGIAR and its partners. AICCRA in Ethiopia aims to strengthen the capacity of targeted national partners and stakeholders of CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa to access and implement at scale validated climate-smart agriculture technologies, climate information services, and climate-informed digital ag-advisories to build the resilience of agri-food systems. The value chains considered for AICCRA project in Ethiopia include beans, wheat, small ruminant and livestock feed and forge options. The AICCRA project in Ethiopia has eight research activities. Livestock feed and forage options value chain contributes to four of the eight activities, which include capacity building to support implementation of climate-smart agriculture (CSA) technology packages; identification of climate- and gender and social inclusion-smartness of CSA packages; prioritization and awareness increase of best-bet CSA options and approaches for key value chains; and integration of climate-smart options and tailored CSI advisory systems for specific value chains. The current report on capacity need assessment is one of the three deliverables that the International Livestock Research Institute (ILRI) Africa RISING research team promised to produce and submit for AICCRA-Ethiopia project in 2021.